Consuming painting : food and the feminine in impressionist Paris - Deutsch, Allison (The Pennsylvania State University Press, 2021)
Metaphor and materiality in nineteenth-century art criticism -- The flesh of painting -- The confected canvas -- Impressionist market gardener.